PENINGKATKAN MINAT BELAJAR MATEMATIKA SISWA KELAS V SD NEGERI PREMBULAN DENGAN MODEL PEMBELAJARAN KOOPERATIF TIPE GROUP INVESTIGATION (GI) - Ika Septi Hidayati; Prihastini Oktasari Putri; Yenny Anggreini Sarumaha (Program Studi Pendidikan Matematika, Fakultas Keguruan dan Ilmu Pendidikan Universitas Cokroaminoto Yogyakarta, 2021)
The purpose of this study was to determine the appropriate application of the GI Type Cooperative learning model in order to increase the learning interest of the fifth grade students of SD Negeri Prembulan. The results of this study indicate that: (1) In general, the application of the appropriate GI learning model is effective in increasing interest in learning mathematics.